The evolution of Indonesian seismic and concrete building codes: From the past to the present. (July 2022) - Nugroho, Wivia Octarena; Sagara, Altho; Imran, Iswandi
Abstract: The factors primarily affecting the seismic vulnerability of existing concrete buildings are the seismic base shear strength which is regulated in the seismic loading codes and the seismic detailing which is regulated through the concrete design codes since both of them are specified and legally enforceable as the minimum standard. This study provides a comprehensive summary of the evolution of the seismic loading and detailing codes for reinforced concrete buildings in Indonesia from 1970 to the present. It specifically focuses on substantial changes in various Indonesian seismic loading and concrete codes for buildings due to the increase in the seismic demand for both strength and ductility. Moreover, lessons learned obtained from the recent two considerable earthquakes, Palu and Lombok earthquakes 2018, were also presented. The main aim is to construct the universal framework of seismic resistance of existing concrete buildings in Indonesia designed through prior versions of Indonesian codes in line with preparing the first Indonesian National Standard (SNI) for seismic evaluation and rehabilitation. The base shear of the low, medium, and high-rise buildings designed using different versions of Indonesian seismic design codes were also compared comprehensively to indicate their significant changes on buildings and identify the possibility of strength deficiency of existing buildings in several big cities in Indonesia which represent most of the seismic zones.